Tiruvalluvar's view on alcoholism - Kanesarajah, K. (university of Jaffna, 2014)
The objective of this research to omit the alcohol habitual behavior. The Sangam poets composed poems on various aspect of human emotions like love, bravery, generosity and eternal beauty of nature. In the post-sangam period, the poets took themes relating to moral principles and rules of conduct. Therefore, the post - sangam period is known as the period of ethical literature. It said that during this period, there were some scholars who described about moral life. Specially Tirukkural holds an important place. It is the book of 1330 couplets by Tiruvallvar with three major chapter. It has been written for the wellbeing of entire humanity. It is a mine of information and It is the foundation of wisdom. At the same time Tiruvallvar emphasis the “Kallunnamai” concept. This study mainly uses an analytic, descriptive and comparative methods in this research. Key words; Alcohol, addiction, disorders, immoral
Keywords: Love; Bravery; Generosity; Moral life